Effect of Wheat (Triticum Aestivum L.) Genotypes on Proximate Composition (SAARC Journal of Agriculture, 2022)
The experiment was conducted during the period from November 2015 to June 2016 at the Laboratory of Biochemistry Department, Sher-e-Bangla Agricultural University (SAU) and Soil Science Laboratory of Bangladesh Agriculture Research Institute (BARI), to find out the effect of different wheat (Triticum aestivum L.) genotypes on proximate composition. Six wheat genotypes, i.e., BARI Gom 25, BARI Gom 26, BARI Gom 27, WYCYT (E-15) (Line), WYCYT (E-16) (Line) and PAVON-76 (Local) were used as a treatment for the experiment. The highest weight of 1000 grains, dry matter content, carbohydrate content, protein content, lipid content, ash content were recorded from BARI Gom 26 (46.45 g), BARI Gom 27 (92.53%), WYCYT (E-16) (69.59%), BARI Gom 27 (10.08%), BARI Gom 26 (2.20%), BARI Gom 26 (2.38%), respectively. Nevertheless, the lowest weight of 1000 grains, dry matter content, carbohydrate content, protein content, lipid content, ash content were recorded from PAVON-76 (Local) (39.25 g), WYCYT (E-15) (Line) (90.43%), BARI Gom 26 (64.87%), WYCYT (E-16) (Line) (9.5%), WYCYT (E-16) (Line) (1.74%), WYCYT (E- 16) (Line) (1.86%), respectively.SAARC J. Agric., 19(2): 171-179 (2021)